2021
DOI: 10.3390/microorganisms9112309
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Metagenomic Next-Generation Sequencing in Patients with Hematologic Malignancies Suffering from Sepsis

Abstract: Background: Sepsis remains a common but fatal complication among patients with immune suppression. We aimed to investigate the performance of metagenomic next-generation sequencing (mNGS) compared with standard microbiological diagnostics in patients with hematologic malignancies. Methods: We performed a prospective study from June 2019 to December 2019. Adult patients with hematologic malignancies and a clinical diagnosis of sepsis were enrolled. Conventional diagnostic methods included blood cultures, serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The detected fungi include Marneffei basket fungus, Aspergillus , and Candida albicans . 17 There were viruses detected from both the clinical concordance group and nonconcordance group, including human γ Herpes virus type 4 (EBV), 18 human α Herpes virus type 1 (HSV1), human β Herpesvirus 6B, human β Herpes virus type 5 (CMV), and various subtypes of the macrocyclic virus, 19 which were detected in both groups. Combined with clinical information, sepsis was not considered.…”
Section: Resultsmentioning
confidence: 99%
“…The detected fungi include Marneffei basket fungus, Aspergillus , and Candida albicans . 17 There were viruses detected from both the clinical concordance group and nonconcordance group, including human γ Herpes virus type 4 (EBV), 18 human α Herpes virus type 1 (HSV1), human β Herpesvirus 6B, human β Herpes virus type 5 (CMV), and various subtypes of the macrocyclic virus, 19 which were detected in both groups. Combined with clinical information, sepsis was not considered.…”
Section: Resultsmentioning
confidence: 99%
“…27 mNGS can detect microorganisms from samples like BLAF, cavity effusion, biopsy tissue, cerebrospinal fluid, urine, blood and sputum. 26,[28][29][30] The application of mNGS for immunocompromised CAP patients could provide a wide range of potential pathogens and improve the prognosis. 30 Haibing Liu and his colleagues found that several antibiotic resistance genes of bacteria by mNGS were consistent with drug sensitivity test.…”
Section: Discussionmentioning
confidence: 99%
“…26,[28][29][30] The application of mNGS for immunocompromised CAP patients could provide a wide range of potential pathogens and improve the prognosis. 30 Haibing Liu and his colleagues found that several antibiotic resistance genes of bacteria by mNGS were consistent with drug sensitivity test. 12 Nowadays, mNGS provide a new insight for a promising pathogenic identification for various infectious disease and is further likely to evaluate immunological competence to offending agents, virulence genes and more antimicrobial genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working on pathogen detection in cerebrospinal fluid (CSF) by mNGS, Miller et al [16] reported a claimed sensitivity of 73% and a claimed specificity of 99%. In some study [17], sensitivity and specificity were not explicitly stated. In this study, a sensitivity of 81.8% was reported.…”
Section: Discussionmentioning
confidence: 99%